2011
DOI: 10.1063/1.3540361
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of switching current by spin transfer torque effect in perpendicular anisotropy magnetoresistive devices (invited)

Abstract: Spin transfer torque-based magnetic random access memory with perpendicular magnetic anisotropy (PMA) provides better scalability and lower power consumption compared to those with in-plane anisotropy. Spin transfer torque switching in magnetoresistive spin valves with PMA is investigated. The hard layer is made of (Co/Pd) multilayer, whereas the soft layer is a lamination of (CoFe/Pd) and (Co/Pd). By the insertion of an in-plane spin polarizer adjacent to the perpendicular anisotropy free layer, thus creating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…The linear behavior for the thicker free layers is consistent with a saturated demagnetization factor N z and the linearly growing volume when increasing the layer thickness [25]. On the other hand for thinner free layers the demagnetization factor is not saturated as compared to thick layers and starts to grow when the thickness is decreased.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The linear behavior for the thicker free layers is consistent with a saturated demagnetization factor N z and the linearly growing volume when increasing the layer thickness [25]. On the other hand for thinner free layers the demagnetization factor is not saturated as compared to thick layers and starts to grow when the thickness is decreased.…”
Section: Resultssupporting
confidence: 68%
“…It can also be observed that for thicker films the linear fit matches very well (linear fit → dashed line, simulation data → solid line), while for a thickness below 2nm a shorter switching time than predicted by the linear fit is found. In order to explain this behavior we assume an exponential dependence of the switching time t ∝ exp(E/k B T ) [24] on the thermal stability barrier E described by [25]:…”
Section: Introductionmentioning
confidence: 99%
“…A strong research effort is currently done within the spintronics community to obtain ever improved magnetic properties 1,2 for optimal utilization in integrated devices like sensors and memories 3 which often rely on Magnetic Tunnel Junctions (MTJ). Often overlooked, the evolution of the magnetic properties with temperature is crucial for achieving high performance MTJ.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] However, in order to implement this system into real application, has to be further improved while lowering the J C . Recently, there have been several efforts in reducing J C of CoFeB-MgO MTJ by incorporating insertion layer 13 for example or by employing electric field (E) assisted switching.…”
Section: Introductionmentioning
confidence: 99%